‘Stay with the body’: facilitating integrative silence in community-based sexual trauma care - Leona Morgan; Sarojini Nadar; Ines Keygnaert (European Journal of Psychotraumatology)
Background: Research has demonstrated that the verbal disclosure for adult victims of childhood sexual trauma (CST) presents significant challenges and seldom provides comprehensive trauma integration. Limited psychosocial support and specialist trauma care particularly in marginalised communities, can further exacerbate the non-disclosure of CST. Although various intervention models for adult victims of CST exist, the potential of facilitating integrative silence as part of community centred integrative trauma informed care (ITIC), remains under-explored.Objective: The objective of this article, is to document how facilitating spaces of integrative silence in a therapeutic context, shifts embodied trauma awareness, comprehensive trauma realisation and trauma integration for adult victims of CST from intergenerational marginalised contexts.Methods: Through participatory action research (PAR), framed in de-colonial feminist community praxis with 13 women aged 21-62, the first author as therapist-researcher facilitated audio-visual recorded semi-structured interviews (n = 13) and integrative trauma informed care (ITIC) follow-up sessions (n = 60) to assess the value of the spoken, unspoken and silence in trauma care. Inductive reflexive thematic analysis and a multistage recursive coding process of verbatim transcriptions, were used to identify embodied trauma awareness before, during, and after periods of silence.Results: The de-colonial, feminist framing for community centred ITIC enhanced participant-specific embodied awareness, establishing a safe space for self-reflection. Contextual sensitivity and careful attention to the therapeutic environment were paramount. The facilitation of non-verbal expression empowered participants to explore alternatives to normative, essentialist and religious narratives that often stigmatise trauma responses. This approach enabled participants to reclaim a sense of agency, improving self-regulation and self-care.Conclusion: This study highlights the potential of integrative silence in community based therapeutic contexts. Future research could explore the role of integrative silence in treating various forms of trauma in different cultural and geographic settings and its integration with other therapeutic modalities to enhance culturally sensitive mental health care.